Metagenomic next-generation sequencing assists in the diagnosis of Cryptococcus pneumonia: Case series and literature review - Wang, Huifen; Yan, Su; Liu, Ying; Li, Yaoguang; Cui, Guangying; Ma, Xiaoxu (Frontiers in Public Health, 2022)
Background: Pulmonary cryptococcosis (PC) was once thought to occur only in patients with immune deficiencies, such as tested positive for the Human Immunodeficiency Virus (HIV). However, in recent years, it has been discovered that more than half of the patients with PC in our nation are individuals with normal immune function. As more and more PC cases are recorded, our diagnosis and treatment approaches, as well as our understanding of PC, are gradually improving. In reality, most PC patients still have a high incidence of misdiagnosis on their initial visit. It is primarily linked to the diverse clinical manifestations, atypical imaging findings, and inaccurate diagnostic approaches. Case Presentation: From 2019 to 2020, we diagnosed three PC patients( three middle-aged males, ages 32 to 41) with normal immunity by histopathological examination and metagenomic next-generation sequencing (mNGS). On admission, they all had pulmonary infection symptoms of varying degrees in their basic condition. But this basic information should not be used as evidence to suspect cryptococcus infection. In two cases, Cryptococcus neoformans was detected using pathological biopsies and mNGS with mNGS being faster than histopathology. In another case, the pathology report was positive but mNGS revealed no pathogen. All three patients were treated with sensitive medicines after the diagnosis, and they all improved and were discharged from the hospital. Subsequent follow-up showed that the patients recovered with good outcomes. Conclusions: Our data demonstrates that mNGS can be used as an auxiliary method for PC diagnosis. Early mNGS aids in the identification of pathogens, enabling early diagnosis and treatment, as well as a reduction in the rate of misdiagnosis and illness progression.